1993
DOI: 10.1039/c39930000929
|View full text |Cite
|
Sign up to set email alerts
|

High ionic conductivity of new polymer electrolytes consisting of polypyridinium, pyridinium and aluminium chloride

Abstract: Polymer complexes consisting of polypyridinium, pyridinium and aluminium chloride are found to be a new class of highly conductive polymer electrolytes, which exhibit a high ionic conductivity of 10-3 S cm-1 at room temperature within range of the conductivity of electrolyte solutions, in spite of film-forming properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 82 publications
(52 citation statements)
references
References 7 publications
0
50
0
2
Order By: Relevance
“…The class of PEs obtained by this method are termed "polymer-in-salt" electrolytes [10], and were independently reported by Angell [11] and one of the authors of this paper [12] in 1993 for the first time. We proposed the use of polymer electrolytes consisting of polymers and ionic liquids (ILs), which are molten salts with melting points lower than 100 C [13][14][15].…”
Section: Introductionmentioning
confidence: 90%
“…The class of PEs obtained by this method are termed "polymer-in-salt" electrolytes [10], and were independently reported by Angell [11] and one of the authors of this paper [12] in 1993 for the first time. We proposed the use of polymer electrolytes consisting of polymers and ionic liquids (ILs), which are molten salts with melting points lower than 100 C [13][14][15].…”
Section: Introductionmentioning
confidence: 90%
“…10 In 1993, the current authors published the first report on a polymer electrolyte having an exceptionally high ionic conductivity at that time, which was a molecular composite consisting of a chloroaluminate IL and a polymer. 11 To the best of our knowledge, this was the first report on the materialization of an IL/synthetic-polymer combination. Subsequently, we found that common vinyl monomers are widely soluble in common ILs and that they can be polymerized in ILs by freeradical polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…Polymer electrolytes 1 have occupied an important position in solid-state ionics because of their unique properties, such as film-forming capabilities, good processibility, flexibility, light weight, elasticity (plasticity), transparency, a relatively high ionic conductivity, and a wide potential window. Some of these characteristics cannot be attained by hard inorganic solid electrolytes, including inorganic glasses, and thus, polymer electrolytes have been exploited to bridge a gap between fluid electrolyte solutions and hard inorganic solid electrolytes.…”
Section: Introductionmentioning
confidence: 99%